Inhibiting Interleukin 11 Signaling Reduces Hepatocyte Death and Liver Fibrosis, Inflammation, and Steatosis in Mouse Models of Non-Alcoholic Steatohepatitis. - Widjaja, Anissa A (2019)
10.1053/j.gastro.2019.05.002